Study of the Structures of Carbon Foams Synthesized Using Non-Ionic Surfactants - Vanessa S. Garcia-Cuello; Liliana Giraldo; Juan C. Moreno-Piraján (Adsorption Science & Technology)
Non-ionic nonylphenol ethoxylate surfactants containing 4, 6, 9 or 12 ethylene oxide residues per mole of nonylphenol were successfully used as templates for the synthesis of large-pore mesoporous carbon foams. The effects of surfactant type, foam resin precursor (phenol/formaldehyde/ethanol), temperature, thermal stability and the number of ethylene oxide residues per mole of nonylphenol on the resulting mesoporous carbon foams were studied in detail. The mesoporous carbon foams were characterized using several techniques, including scanning electron microscopy and nitrogen adsorption/desorption analysis. The present work showed that the number of ethylene oxide units on the surfactant template strongly affected the pore diameter and that the pore diameter, in turn, depended strongly on the heating time and temperature.